A validation study of after direct‐acting antivirals recommendation for surveillance score for the development of hepatocellular carcinoma in patients with hepatitis C virus infection who had received direct‐acting antiviral therapy and achieved sustained virological response. Issue 1 (8th December 2021) - Tada, Toshifumi; Kurosaki, Masayuki; Tamaki, Nobuharu; Yasui, Yutaka; Mori, Nami; Tsuji, Keiji; Hasebe, Chitomi; Joko, Koji; Akahane, Takehiro; Furuta, Koichiro; Kobashi, Haruhiko; Kimura, Hiroyuki; et al.
Abstract: Background and Aim: The pathogenic process underlying the development of hepatocellular carcinoma (HCC) is not yet clear in patients with hepatitis C virus (HCV) who have received direct‐acting antiviral (DAA) therapy and achieved sustained virological response (SVR). This study validated a composite predictive model for HCC in these patients. Methods: This study included 3058 patients in whom HCV was eradicated with DAA therapy. After DAAs recommendation for surveillance (ADRES) score, which is based on sex, FIB‐4 index, and α‐fetoprotein, was used as a composite predictive model for HCC development. Results: The 1‐, 3‐, and 5‐year cumulative incidence rates of HCC were 0.9, 4.5, and 15.2%, respectively. Multivariate analysis with Cox proportional hazards models showed that male sex (hazard ratio [HR], 2.646; 95% confidence interval [CI], 1.790–3.911), FIB‐4 index >3.25 (HR, 2.891; 95% CI, 1.947–4.293), and α‐fetoprotein >5 ng/mL (HR, 2.835; 95% CI, 1.914–4.200) are independently associated with HCC development. The incidence of HCC differed significantly by ADRES score ( P < 0.001). Cox proportional hazards models showed that compared to the ADRES score 0 group, the HR for HCC development was 2.947 (95% CI, 1.367–6.354) in the ADRES score 1 group, 9.171 (95% CI, 4.339–19.380) in the ADRES score 2 group, and 20.630 (95% CI, 8.641–49.230) in the ADRES score 3 group. ADRES score had superior predictive power for HCC development compared with the FIB‐4 index and α‐fetoprotein according to time‐dependent receiver operating characteristic analysis. Conclusion: The ADRES score is useful for predicting HCC development after SVR. Abstract : This study aimed to validate the utility of the after direct‐acting antivirals recommendation for surveillance (ADRES) score for predicting hepatocellular carcinoma (HCC) development in patients who had received direct‐acting antiviral therapy and achieved sustained virological response. The incidence of HCC differed significantly by ADRES score in this patient population. ADRES score had higher predictive power for the development of HCC than the FIB‐4 index and a‐fetoprotein according to time‐dependent receiver operating characteristic analysis.